A Novel INCNS Score for Prediction of Mortality and Functional Outcome of Comatose Patients - Zhao, Zhihan; Zhang, Xiao; Song, Changgeng; Zhao, Jingjing; Gao, Qiong; Jiang, Wen (Frontiers in Neurology, 2021)
Objectives: The purpose of this study was to verify the veracity and reliability of the INCNS score for prediction of neurological ICU (NICU) mortality and 3-month functional outcome and mortality in comatose patients. Methods: In this prospective study, data of the patients admitted to NICU from January 2013 to January 2019 were collected for validation. The 3-month functional outcomes were evaluated using modified Rankin Scale (mRS). By using the receiver operating characteristics curve (ROC) analysis, we compared the INCNS score with Glasgow Coma Scale (GCS), Full Outline of Un-Responsiveness Score (FOUR) and Acute Physiology and Chronic Health Evaluation II (APACHE II) for assessment of the predictive performance of these scales for 3-month functional outcome and mortality and NICU mortality performed at 24- and 72-h after admission to the NICU. Results: Totally 271 patients were used for evaluation; the INCNS score achieved an AUC (area under the receiver operating characteristic curve) of 0.766 (95% CI: 0.711–0.815) and 0.824 (95% CI: 0.774–0.868) for unfavorable functional outcomes, an AUC of 0.848 (95% CI: 0.800–0.889) and 0.892 (95% CI: 0.848–0.926) for NICU mortality, and an AUC of 0.811 (95% CI: 0.760–0.856) and 0.832 (95% CI: 0.782–0.874) for the 3-month mortality after discharge from the NICU at 24- and 72-h. The INCNS score exhibited a significantly better predictive performance of mortality and 3-month functional outcomes than FOUR and GCS. There was no significant difference in predicting NICU mortality and 3-month functional outcomes between INCNS and APACHE II, but INCNS had better predictive performance of 3-month mortality than APACHE II. Conclusions: The INCNS score could be used for predicting the functional outcomes and mortality rate of comatose patients.